2018
DOI: 10.3389/fninf.2018.00044
|View full text |Cite
|
Sign up to set email alerts
|

Exoskeleton-Robot Assisted Therapy in Stroke Patients: A Lesion Mapping Study

Abstract: Background: Technology-supported rehabilitation is emerging as a solution to support therapists in providing a high-intensity, repetitive and task-specific treatment, aimed at improving stroke recovery. End-effector robotic devices are known to positively affect the recovery of arm functions, however there is a lack of evidence regarding exoskeletons. This paper evaluates the impact of cerebral lesion load on the response to a validated robotic-assisted rehabilitation protocol.Methods: Fourteen hemiparetic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Then, many of the neurorehabilitation studies that employed emerging robotic solutions did not account for a complete characterization of brain activity. Some studies exist [166][167][168], but further efforts are required [166] to characterize the neural basis of the sensorimotor function recovery driven by novel robotic devices. An unmet interest is understanding how the structural and functional properties of the brain are sculpted by the rehabilitation program.…”
Section: Multimodal Assessment Of Recoverymentioning
confidence: 99%
“…Then, many of the neurorehabilitation studies that employed emerging robotic solutions did not account for a complete characterization of brain activity. Some studies exist [166][167][168], but further efforts are required [166] to characterize the neural basis of the sensorimotor function recovery driven by novel robotic devices. An unmet interest is understanding how the structural and functional properties of the brain are sculpted by the rehabilitation program.…”
Section: Multimodal Assessment Of Recoverymentioning
confidence: 99%
“…Robot-assisted rehabilitation has become increasingly popular in recent decades, and there are more and more therapy concepts that attributed to various novel rehabilitation robots (Shields et al, 1997; DiCicco et al, 2004; Wege and Hommel, 2005; Hasegawa et al, 2008; Chiri et al, 2009; Tadano et al, 2010; Brokaw et al, 2011; In et al, 2011; Kadowaki et al, 2011; Ueki et al, 2012; Villafañe et al, 2017; Cerasa et al, 2018; Jakob et al, 2018; Mazzoleni et al, 2018; Pila et al, 2018). In robot-assisted rehabilitation, patients can receive standardized and repetitive training controlled by robot actuators (Takahashi et al, 2005; Chang and Kim, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This device has been widely validated (Colizzi et al., 2009; Dolce et al., 2009; Pignolo et al., 2012) with respect to conventional neurorehabilitation approaches. In agreement with previously validated version [6,[11], [12], [13]], the ARAMIS protocol for rehabilitation included 60-min sessions over periods not exceeding 7 weeks. Copernicus is a system for the correct load balancing aimed at obtaining an early start of locomotion (http://www.rehalife.it/en/products). The patient wears a pair of insoles in his or her shoes equipped with piezoresistive sensors that detect the support of the foot and transfer the information via Wi-Fi to a controller with a monitor (tablet) that is visual feedback for the patient when executing the various rehabilitation exercises.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Following previously validated protocol [6], we performed a double-blind randomized controlled trial divided into 5 principal stages. The first stage was based on the recruitment of the patients for the study (see inclusion criteria reported above).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%